2022
DOI: 10.3389/fnins.2022.949575
|View full text |Cite
|
Sign up to set email alerts
|

Brain-machine interface-based training for improving upper extremity function after stroke: A meta-analysis of randomized controlled trials

Abstract: BackgroundUpper extremity dysfunction after stroke is an urgent clinical problem that greatly affects patients' daily life and reduces their quality of life. As an emerging rehabilitation method, brain-machine interface (BMI)-based training can extract brain signals and provide feedback to form a closed-loop rehabilitation, which is currently being studied for functional restoration after stroke. However, there is no reliable medical evidence to support the effect of BMI-based training on upper extremity funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…The majority turned out to be literatures reviews on Assistive BCI systems. Due to the large quantity of review articles, the authors combined all the review articles' (Cervera et al, 2018 ; Bai et al, 2020 ; Kruse et al, 2020 ; Baniqued et al, 2021 ; Behboodi et al, 2022 ; Mansour et al, 2022 ; Peng et al, 2022 ; Xie et al, 2022 ) studies/reports. The eight literature reviews produced 32 unique research articles that were within the scope of this sub-review, and they are described in Supplementary Table V .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority turned out to be literatures reviews on Assistive BCI systems. Due to the large quantity of review articles, the authors combined all the review articles' (Cervera et al, 2018 ; Bai et al, 2020 ; Kruse et al, 2020 ; Baniqued et al, 2021 ; Behboodi et al, 2022 ; Mansour et al, 2022 ; Peng et al, 2022 ; Xie et al, 2022 ) studies/reports. The eight literature reviews produced 32 unique research articles that were within the scope of this sub-review, and they are described in Supplementary Table V .…”
Section: Resultsmentioning
confidence: 99%
“…These studies have small sample sizes, short intervention durations, and interpretation difficulty of results due to many factors (e.g., severity of stroke, acuity of stroke, protocol of the intervention, etc. ), which leads to a lack of evidence in proving the effectiveness of these systems and discourages medical companies and hospitals from using them in their routine treatments (Mcconnell et al, 2017 ; Hu et al, 2022 ; Xie et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the stroke, the patient's brain structure and connectivity have changed. Related studies have found that, the plasticity of the brain provides a basis for rehabilitation after stroke (Xie et al, 2022 ), as time goes on, the brain tissue has a certain ability to repair itself (Hermann and Chopp, 2012 ). Acupuncture combined with balloon dilatation may promote this compensation and repair mechanism, and reorganize the brain function of stroke patients (Zhang et al, 2021 ), thus improving swallowing function, promoting rapid recovery of patients, and shortening the disease's course.…”
Section: Discussionmentioning
confidence: 99%
“…They mainly analyzed robot, FES, and visual feedback, and the results indicated that only BCIs triggering the stimulation of FES had a significantly larger effect size on motor function recovery, compared with control interventions. In Xie's meta-analysis [48], they considered BCI combined with FES or visual feedback may be a better combination for functional recovery than a robot.…”
Section: Discussionmentioning
confidence: 99%